Perlindungan Hukum Hak Pemegang Saham Dalam Pembubaran Perusahaan Berdasarkan Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas (Studi Kasus Putusan Mahkamah Agung Nomor 1618 K/PDT/2016) - Tengku Agung Kurniawan (Kertha Wicaksana, 2022)
The dissolution of a limited liability company is regulated in Article 142-146 of Law Number 40 of 2007 concerning Limited Liability Companies. In the case of the Supreme Court Decision Number 1618 K/Pdt/2016 where one of the requirements for the application for the dissolution of a Limited Liability Company is to notify the tax agency that the company has been inactive for 3 (three) years or more which must be carried out by the Board of Directors. Whereas in the case of the dissolution of the company through a court order in article 146 paragraph 1 letter c it states that the district court may dissolve the company at the request of the shareholders, the Board of Directors or the Board of Commissioners based on the reasons that the company is not possible to continue. The formulation of the problem in this study is first, how is legal certainty to shareholders, due to the lack of clarity on who is entitled to apply for the dissolution of a limited liability company (case study of the Supreme Court's decision number 1618 k/pdt/2016, secondly, how is the legal protection for shareholders, in the case of dissolution of the company). the company in particular regarding the parties entitled to apply for the dissolution of the limited liability company (case study of the Supreme Court's decision number 1618 k/pdt/2016). In this study using a normative legal research method, namely by studying literature. The results of the study concluded that to truly guarantee legal certainty in To protect the rights of shareholders as a result of the dissolution of a company, a law, in addition to meeting formal requirements, must also meet other requirements, namely clear in its formulation, consistent in its formulation both internally and externally, use of appropriate language and easy to understand by people who read it. anya. Legal protection for shareholders, in the dissolution of the company, especially regarding the parties entitled to apply for the dissolution of the limited liability company (Case Study of Supreme Court Decision Number 1618 K/Pdt/2016) that the losses suffered by shareholders are very large losses which have implications for the development of the decision sector. The decision must provide legal protection to the shareholders. The law is made by the ruler and there is an order that must be obeyed, the judge must comply with the regulations that have been made by the authorities through laws and regulations which specifically in this case are subject to Law Number 40 of 2007 concerning Limited Liability Companies.